2003
DOI: 10.1038/sj.bjp.0705419
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone and 15‐deoxy‐Δ12,14‐prostaglandin J2, ligands of the peroxisome proliferator‐activated receptor‐γ (PPAR‐γ), reduce ischaemia/reperfusion injury of the gut

Abstract: The peroxisome proliferator‐activated receptor‐γ (PPAR‐γ) is a member of the nuclear receptor superfamily of ligand‐dependent transcription factors related to retinoid, steroid and thyroid hormone receptors. The thiazolidinedione rosiglitazone and the endogenous cyclopentenone prostaglandin (PG)D2 metabolite, 15‐deoxy‐Δ12,14‐PGJ2 (15d‐PGJ2), are two PPAR‐γ ligands, which modulate the transcription of target genes. The aim of this study was to investigate the effect of rosiglitazone and 15d‐PGJ2 on the tissue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 43 publications
5
53
0
Order By: Relevance
“…Additionally, previous studies indicates that ligand-activated PPAR-g can downregulate NF-kB transcription [10,14]. In line with these fi ndings, in vivo treatment with rosiglitazone has been shown to attenuate the development of acute infl ammation [15], the development of zymosan-induced nonseptic shock [16], and the degree of ischemia-reperfusion injury in gut [17]. More recently, Birrell et al [18] have reported that PPAR-g agonists, rosiglitazone and SB 219994, inhibit aerosolized LPS-induced airway neutrophilia and associated release of pro-infl ammatory cytokines (granulocytecolony stimulating factor and keratinocyte-derived chemokine) in the mouse lung.…”
Section: Introductionsupporting
confidence: 64%
“…Additionally, previous studies indicates that ligand-activated PPAR-g can downregulate NF-kB transcription [10,14]. In line with these fi ndings, in vivo treatment with rosiglitazone has been shown to attenuate the development of acute infl ammation [15], the development of zymosan-induced nonseptic shock [16], and the degree of ischemia-reperfusion injury in gut [17]. More recently, Birrell et al [18] have reported that PPAR-g agonists, rosiglitazone and SB 219994, inhibit aerosolized LPS-induced airway neutrophilia and associated release of pro-infl ammatory cytokines (granulocytecolony stimulating factor and keratinocyte-derived chemokine) in the mouse lung.…”
Section: Introductionsupporting
confidence: 64%
“…These protective effects are attenuated by PPARγ antagonists or reduction of PPARγ levels in mutant PPARγ heterozygous animals (32,34). Similarly, activation of PPARα attenuates I/R injury by reducing ICAM-1 expression, peroxynitrite activity, and the production of proinflammatory cytokines (35).…”
Section: Models Of Intestinal I/r Injury Pparγ Activation Downregulamentioning
confidence: 98%
“…Ligands for PPAR-γ include natural compounds such as eicosanoids, oxidized phospholipids, 15-deoxy-Δ12,14-PGJ2 and drugs such as the thiazolidinedione derivative rosiglitazone [8], and have been reported to ameliorate ischemia and reperfusion injury in a PPAR-γ dependent manner. The PPAR-γ antagonist, bisphenol A diglycidyl ether (BADGE) abolishes the protection afforded by rosiglitazone and 15d-PGJ2 in a rat model of intestinal I/R [49]. Moreover, rosiglitazone (10 mg/kg) inhibits stomach I/R injury in the heterozygous PPAR-γ-deficient mice, even via activation of reduced levels of PPAR-γ [50].…”
Section: Discussionmentioning
confidence: 99%